Поняття процесуальних норм та їх місце в адміністративному праві - Куценко, С.І. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Рассматриваются взгляды современных исследователей на понятие административно-процессуальной нормы, ее признаки и место в административном праве. Проанализированы особенности административно-процессуальных норм, основания для выделения их в отдельную область права. The author reviews the opinions of modern researchers of the concept of administrative procedural norm, its characteristics and place in administrative law. The author analyzes the peculiarities of administrative procedural norms and gives the view of different approaches towards their determination. Grounds for extraction of administrative procedural norms to separate branch of law are analyzed.